A sala interdisciplinar de aprendizagem no projeto do observatório da educação/capes/UEA: os conhecimentos matemáticos a partir da resolução de problemas - Mota, Denise Medim da (2014)
The mathematics education today faces serious difficulties. Overcome the scientific knowledge to know the knowledge of the school presents itself as one of the great challenges of the teacher of this discipline, especially when he has an academic education that predominated forms of education based on rote learning. This research is characterized by the articulation between interdisciplinarity and Troubleshooting as a way to contribute to the learning of mathematical knowledge. Was performed with students from ninth grade of elementary school from a public school in the city of Manaus / AM in Project Education Observatory (PEO) in order to investigate: From Problem Solving as a teaching strategy in an interdisciplinary perspective, how is the learning of mathematical knowledge? Aimed to understand how is the learning of mathematical knowledge taking as reference the Problem Solving as a teaching strategy in an interdisciplinary perspective, developed in a classroom of mathematical knowledge conceived as a space for study and research, from dialogical situations with the fields of knowledge of Portuguese and Sciences. We anchor our theoretical framework in Japiassu (1976), Farm (2012), Lück (2010), Tomaz and David (2012), Mendes (2009), Dante (2008), among others. The methodological approach is qualitative research method having the action research as mode. As techniques of data collection we have the round of conversation, participant observation, document analysis, questionnaires and interviews. For data analysis was used the technique of content analysis. The results indicate that an education directed to the development of interdisciplinary practice affords students greater ownership of mathematical knowledge. They interact in the proposed activities and the barriers between teacher and student, as evidenced in Mathematics classes are eliminated, because the student actively participates in the construction of their own knowledge. The interdisciplinary approach makes the student able to solve problems independently.